2019
DOI: 10.2737/pnw-rn-579
|View full text |Cite
|
Sign up to set email alerts
|

Scale of monitoring influences interpretation of stream habitat restoration results for juvenile Chinook salmon

Abstract: Stream habitat restoration in the Entiat River, Washington, has increased juvenile Chinook abundance in pools with engineered logjams (ELJs); however, high spatial, temporal, and inter-species variation complicates distinguishing treatment effects between restored and unrestored habitat. Here we show that the scale of post restoration effectiveness monitoring can also be a confounding factor in such studies.In three stream reaches, we conducted snorkel surveys of (1) spatially randomized untreated habitat in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…The unrestored reach (river km 5.2-5.5) has N = 11 natural pools usually formed between small boulders, lacking wood cover, and smaller than the ones created by the structures in the restored reach (mean area = 15.4, range = 3.1-42.6 m 2 ). Polivka et al (2015), Polivka et al (2019), and Polivka and Claeson (2020) showed that unrestored habitat units in much of the lower geomorphic valley segment of the river basin are statistically indistinguishable in terms of fish density, independent of reach. Thus, the reach association of the restored and unrestored pools is a convention for identification rather than an experimental effect.…”
Section: Study Systemmentioning
confidence: 96%
See 1 more Smart Citation
“…The unrestored reach (river km 5.2-5.5) has N = 11 natural pools usually formed between small boulders, lacking wood cover, and smaller than the ones created by the structures in the restored reach (mean area = 15.4, range = 3.1-42.6 m 2 ). Polivka et al (2015), Polivka et al (2019), and Polivka and Claeson (2020) showed that unrestored habitat units in much of the lower geomorphic valley segment of the river basin are statistically indistinguishable in terms of fish density, independent of reach. Thus, the reach association of the restored and unrestored pools is a convention for identification rather than an experimental effect.…”
Section: Study Systemmentioning
confidence: 96%
“…This is an important basis for evaluation, but much of the literature shows small or no effects of restoration when only distribution and density are considered (Roni et al 2008, Whiteway et al 2010, Stranko et al 2012. Furthermore, the inferential power of the results is limited by inadequate replication of structures and/or observational scale mismatched with treatment scale (Roni et al 2002, McMillan et al 2013, Freedman et al 2016, Polivka et al 2019, limiting the ability to detect and quantify the seasonal, annual, and among-species distribution patterns (Bradford and Higgins 2001). This does not necessarily indicate poorly placed or targeted restoration activities, but rather the need for consideration of more robust metrics, including those that more directly describe habitat selection (Conrad et al 2011, Kotler et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…In both of those cases, increases in habitat capacity result in the reach as a whole gaining fi sh. However, this effect may be isolated to the treated pools (Polivka et al 2019 ), as opposed to increasing density in all habitats in the treated reach (Figure 2 ).…”
Section: Approach 2 -"If You Built It and They Came Did Habitat Capac...mentioning
confidence: 99%
“…One persistent question is whether studies at smaller scales (e.g., stream reaches) can be scaled up to make whole river basin inferences (Roni et al 2015b ). Inappropriately scaled studies can lead to some of the ambiguity and variability in results discussed above (Polivka et al 2019 ;Foote et al 2020 ). Modeling efforts to understand salmonid population dynamics, including large-scale lifecycle models, seek to understand the infl uence of, for example, habitat capacity on those dynamics (Scheuerell et al 2006 ;Honea et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation